The Role of Computed Tomography in Imaging Non-neurologic Disorders of the Head in Equine Patients - Stieger-Vanegas, Susanne M.; Hanna, Ashley L. (Frontiers in Veterinary Science, 2022)
Computed tomography (CT) imaging of the head in equine patients is now commonly performed as CT scanners are more readily available. Head CT has proven valuable in evaluating spatially complex anatomic structures, where radiographic superimposition, or restricted access via endoscopy or ultrasound, limit complete evaluation of the disease process. Head CT has been demonstrated to be incredibly valuable in the evaluation of dental and paranasal sinus disease, in disease of the hyoid apparatus and ear, and in evaluation of skull trauma. CT is an excellent modality for assessment of both osseous and soft tissue structures; however, evaluation of complex vascular anatomy and determination of tissue viability is limited without the use of contrast. Therefore, various contrast agent protocols including intravenous and intraarterial iodinated contrast administration techniques have been established. CT also has limitations in the evaluation of brain and spinal cord disease, for which magnetic resonance imaging (MRI) has major advantages. Head CT images are most commonly evaluated in transverse planes. However, standard multiplanar reconstructions of the head including dorsal and parasagittal planes improve the understanding of spatially complex disease processes. These reconstructions can be crucial for accurate identification of diseased teeth and determination of the extent and severity of osseous and paranasal sinus disease. Head CT examinations are becoming an increasingly important diagnostic tool in the evaluation of horses with head pathologies, and CT imaging findings are an important aspect in the clinical decision-making process. The following review discusses the indications, benefits, and technical considerations for the use of computed tomography (CT) in evaluating non-neurologic head pathologies in equine patients.